Stress intensity factor for a curvilinear edge crack in bonded planes subjected to tear stress - Nur Hazirah Husin; Nik Mohd Asri Nik Long; Norazak Senu; Khairum Hamzah (Penerbit Universiti Kebangsaan Malaysia, 2025)
The singular integral equation (SIE) for a curvilinear edge crack that emerges at the interface of bonded planes under tear stress is formulated by making use of the modified complex potential (MCP) and the continuity conditions of displacement and traction. In the formulation of SIE, the unknown is the dislocation distribution function, while traction serves as the right-hand term. The obtained SIE is solved numerically by a semi-open quadrature rule. Numerical results are presented graphically to demonstrate the behaviour of dimensionless stress intensity factors (SIFs) for Modes I and II with different edge crack configurations and elastic constant ratios.